The Abstract Book of the XX Conference for Junior Scientists in Psychology - Kairytė, Agnietė; Mikučionytė , Dovilė; Nomeikaitė, Augustė (Vilnius University Proceedings, 2023)
Conference for Junior Scientists in Psychology is an annual event organized by Ph.D. students at Vilnius University, Institute of Psychology. The conference gives an opportunity for psychology students and junior researchers from various universities in Lithuania to present their scientific work and findings. In 2023, the conference focused on the importance of community and collaboration in research work.